Zrinjka Glovacki-Bernardi, August Kovačec, Ranko Matasović, Milan Mihaljević, Dieter W. Halwachs, Karl Sornig, Christine Penzinger, Richard Schrodt: Uvod u lingvistiku, 2., prošireno izdanje - Novak, Kristian (Array, 2008)
Prikaz drugoga izdanja knjige "Uvod u lingvistiku" grupe autora